COMMD proteins: COMMing to the scene - Maine, Gabriel N. (2007)
COMM Domain containing or COMMD proteins are a recently discovered group of factors defined by the presence of a unique motif in their extreme carboxy termini (COpper Metabolism MURR1 or COMM domain). This protein family is comprised of ten members which are widely conserved throughout evolution and share certain functional properties. At the present time, a number of seemingly discrete functions have been ascribed to these factors. These include the regulation of such events as the activity of the transcription factor NF-κB, copper homeostasis, the function of the epithelial sodium channel, and cell proliferation. A unifying mechanism that would explain all these events is lacking at the moment, but recent studies suggest the possibility that regulation of the ubiquitin pathway may be at the basis of many of the functions of the COMMD protein family.